14-19 Centre Research Study: educational reforms in schools and colleges in England - Baird, J; Elwood, J; Duffy, G; Feiler, A; O'Boyle, A; Rose, J; Stobart, G; McWhirter, A (University of Bristol, 2011)
The key aims of the 14-19 educational reform programme (DCSF, 2005 and 2008a) were to transform the 14-19 phase of education and training to provide better and more applicable educational experiences for all young people and to raise aspirations as well as quality and standards at this phase. These aims were part of wider goals to make England ‘the best place in the world for children and young people to grow up’ as well as putting the ‘the needs of children, young people and parents at the centre of everything we do’ (DCSF, 2008a: 4) The primary aim of the Centre Research Study (hereafter referred to as the ‘CReSt project’) was to study the impact of the 14-19 Educational Reforms as a whole upon educational institutions in England over the five-year implementation period (2009-14). This QCDA project began with previous, ‘baseline’ studies, which were conducted by two teams of researchers who studied mainstream and special schools respectively (Gorard et al, 2008; QCDA, 2009). The case reports and final reports from these studies informed the current research, as they described the circumstances and contexts of a sample of institutions prior to the 14-19 reform programme. An unusual aspect of the CReSt project is that it has a broader perspective than the evaluation of any particular reform and takes stock of the complementary and competing effects of the many reforms that affect educational institutions at any time. Separate evaluations of the individual reforms were (or are being) conducted by other research teams (information on which can be obtained from QCDA). As such, the CReSt project aims to take a broad view of the effects upon educational institutions and is not designed to assess the impact of any single policy.